Isolation and Characterization of a Shigella flexneri Invasin Complex Subunit Vaccine - Turbyfill, K. Ross (American Society for Microbiology, 2000)
The invasiveness and virulence of Shigella spp. are largely due to the expression of plasmid-encoded virulence factors, among which are the invasion plasmid antigens (Ipa proteins). After infection, the host immune response is directed primarily against lipopolysaccharide (LPS) and the virulence proteins (IpaB, IpaC, and IpaD). Recent observations have indicated that the Ipa proteins (IpaB, IpaC, and possibly IpaD) form a multiprotein complex capable of inducing the phagocytic event which internalizes the bacterium. We have isolated a complex of invasins and LPS from water-extractable antigens of virulent shigellae by ion-exchange chromatography. Western blot analysis of the complex indicates that all of the major virulence antigens of Shigella, including IpaB, IpaC, and IpaD, and LPS are components of this macromolecular complex. Mice or guinea pigs immunized intranasally with purified invasin complex (invaplex), without any additional adjuvant, mounted a significant immunoglobulin G (IgG) and IgA antibody response against the Shigella virulence antigens and LPS. The virulence-specific response was very similar to that previously noted in primates infected with shigellae. Guinea pigs (keratoconjunctivitis model) or mice (lethal lung model) immunized intranasally on days 0, 14, and 28 and challenged 3 weeks later with virulent shigellae were protected from disease (P < 0.01 for both animal models).